IPTEKS PERLAKUAN AKUNTANSI TERHADAP PENGHENTIAN DAN PELEPASAN ASET TETAP PADA KANTOR LURAH KLEAK - Mararu, Gandi; Pontoh, Winston (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Fixed assets are one of several conditions that can support the success of companies and agencies. With adequate fixed assets, the smooth running of the business and operational activities of a company or agency can run well. The Kleak village office must have fixed assets that have expired, obsolete, and economically depleted, and whether the Kleak village office has released and terminated the assets according to PSAK NO. 16. The result shows that Kleak vilage office has never terminated and released the fixed assets which have expired or have been obsolete.Keywords: Release of fixed assets, PSAK NO. 16